Physical pharmacy : physical chemical principles in the pharmaceutical sciences - Martin, Alfred (Lippincott Williams & Wilkins, 1993)
The book is an improvement over the last edition, but it does not hit the target audience of the professional pharmacy student. This is because of the large number of changes in the profession of pharmacy. For this book to be of value to students of pharmacy, the principles that are covered need to be related to dosage formulations and situations they may encounter in practice. There are many important colloidal formulations, suspensions, and emulsions that could have been use to demonstrate these principles, but they were not mentioned. Some of the problems do not seem applicable, e.g., the electrolyte calculations in the nonelectrolyte chapter.